2022
DOI: 10.1111/add.16075
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent validity of the marijuana purchase task: a meta‐analysis of trait‐level cannabis demand and cannabis involvement

Abstract: Background and aims The Marijuana Purchase Task (MPT) is increasingly used to measure cannabis reinforcing value and has potential use for cannabis etiological and regulatory research. This meta‐analysis sought to evaluate for the first time the MPT's concurrent validity in relation to cannabis involvement. Methods Electronic databases and pre‐print repositories were searched for MPT studies that examined the cross‐sectional relationship between frequency and quantity of cannabis use, problems, dependence, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…The evidence also suggests that intensity and O max appear more reliable than break point, P max , and α. This is notable given recent meta‐analyses reporting that intensity and O max typically have the strongest associations with alcohol, cannabis, and tobacco use variables (e.g., González‐Roz et al, 2019; González‐Roz et al, 2022; Martínez‐Loredo et al, 2021). Finally, our review revealed differences in the extent to which specific demand indices were reliable or valid.…”
Section: General Discussion and Future Directionsmentioning
confidence: 94%
See 1 more Smart Citation
“…The evidence also suggests that intensity and O max appear more reliable than break point, P max , and α. This is notable given recent meta‐analyses reporting that intensity and O max typically have the strongest associations with alcohol, cannabis, and tobacco use variables (e.g., González‐Roz et al, 2019; González‐Roz et al, 2022; Martínez‐Loredo et al, 2021). Finally, our review revealed differences in the extent to which specific demand indices were reliable or valid.…”
Section: General Discussion and Future Directionsmentioning
confidence: 94%
“…We recognize behavioral economists have also been concerned with the predictive validity (e.g., MacKillop & Murphy, 2007;Murphy et al, 2015) and concurrent validity (e.g., Gonz alez-Roz et al, 2019;Gonz alez-Roz et al, 2022;Martínez-Loredo et al, 2021). Though important, these topics exceed the scope of our review.…”
Section: Test-retest Reliabilitymentioning
confidence: 94%
“…Although behavioral economic demand for cannabis is a robust predictor of cannabis consumption and CUD severity (Aston & Berey, 2022; Aston et al, 2015; González-Roz et al, 2022), few studies have examined factors that are associated with individual differences in cannabis demand. This is the first study to our knowledge to examine associations between EFs (i.e., inhibitory control, set shifting, working memory) and indices of cannabis demand.…”
Section: Discussionmentioning
confidence: 99%
“…Five related indices of behavioral economic cannabis demand may be obtained from the MPT: intensity (i.e., cannabis consumption at zero cost), O max (i.e., peak expenditure on cannabis), P max (i.e., price corresponding to peak expenditure on cannabis), breakpoint (i.e., the cost at which cannabis consumption is suppressed to zero), and elasticity (i.e., the sensitivity of consumption to cost, or the degree to which consumption of cannabis decreases as price increases; Aston et al, 2015; Collins et al, 2014). These demand indices, and especially O max , intensity, and elasticity, are robustly associated with patterns of cannabis use, including quantity and frequency of use, craving, and symptoms of CUD, in a variety of populations including young adults (Aston & Berey, 2022; Aston et al, 2015; González-Roz et al, 2022; Minhas et al, 2021; Strickland et al, 2017; Zvorsky et al, 2019).…”
Section: The Present Studymentioning
confidence: 99%
“…Given that lower prices of cannabis products may constitute a potential incentive for increased purchases, especially for high‐risk users [10], it is of interest how cannabis prices are regulated in CSC. Analysing a unique cross‐sectional data set from CSC in Barcelona, Spain, this study was guided by the following research questions: How do cannabis prices in CSC in Barcelona compare to national estimates (from the illicit market)? Can quantity discounts be observed in CSC? …”
Section: Introductionmentioning
confidence: 99%